THE COMPOSITION AND STRUCTURE OF SODIUM DODECYL-SULFATE DODECANOL MIXTURES ADSORBED AT THE AIR-WATER-INTERFACE - A NEUTRON REFLECTION STUDY - Lu, J; Purcell, I; Lee, E; Simister, E; Thomas, R; Rennie, A; Penfold, J (1995)
Neutron reflection has been used to study the composition of layers of sodium dodecyl sulfate (SDS) and dodecanol mixtures adsorbed at the air/water interface. Saturation of the surface by dodecanol at a 6.7 mM SDS concentration occurs when the bulk dodecanol concentration is about four times the solubility of dodecanol in pure water, indicating that even below the cmc dodecanol is solubilized by SDS. At a fixed dodecanol/SDS ratio the adsorption of dodecanol passes through a maximum at about half the cmc as the SDS concentration is changed, dropping sharply, although not to zero, at the cmc. Above the cmc it is estimated that an average of about two dodecanol molecules are incorporated into a single micelle. The adsorption of SDS is affected by the presence of dodecanol. At low SDS concentrations (<1 mM) the SDS adsorption is enhanced but at higher concentrations it is reduced by about 10%. The former observation shows that there is a very strong attractive interaction between dodecanol and SDS and the overall adsorption behavior of dodecanol and of SDS at low SDS concentrations is satisfactorily explained in terms of the formation of an SDS/dodecanol complex and Langmuir adsorption of dodecanol and the complex at the surface. As an example, at an SDS concentration of 0.0001 M, when the amount of dodecanol is 0.5% of the SDS, about one-third of the total surface excess of 1.9 × 10-10 mol cm-2 is in the form of the 1:1 complex. The structure of the mixed layer has been investigated at a single composition and compared with the structure in the absence of dodecanol. The thickness of the dodecanol region of the layer (19 Å) is slightly greater than the length of the fully extended dodecanol molecule and the thickness of the SDS region increases on addition of dodecanol. Both these effects result from an increased roughness of the layer compared with pure SDS. The center of the dodecanol distribution is 3.5 Å further away from the water than the center of the SDS distribution. This is intermediate between what would be expected for a second surfactant and the value of 6.5 Å observed for a nonionic additive (dodecane and dodecyl trimethylammonium bromide). © 1995 Academic Press. All rights reserved.